Protection of The Notary Position in Monitoring Beneficial Ownership to Prevent The Misuse of Issued Documents - Puspita, Lidya; Sudirman, Maman; Djaja, Benny (Universitas Islam Malang, 2024)
A notary is a public official authorized to create authentic deeds and perform other actions in accordance with the law. Given the significant responsibilities they bear, notaries require legal protection while performing their duties, particularly in applying the Principle of Identifying the Ultimate Beneficial Owner of a legal entity. This protection is crucial for reducing legal risks and supporting the implementation of Presidential Regulation Number 13 of 2018, which aims to combat Money Laundering and Terrorism Financing. This paper analyzes issues related to the application of the Principle of Identifying the Ultimate Beneficial Owner by notaries, including the importance of applying this principle and how the Beneficial Ownership Declaration can protect notaries from legal claims. The study uses a normative juridical method with a comparative approach, concluding that the application of this principle is important for notaries. Position of Notary Act as gatekeepers who can help prevent or mitigate undesired risks by obtaining accurate information about the parties involved. However, the legal protection provided by the Beneficial Ownership Declaration is not entirely effective.